2003
DOI: 10.1034/j.1399-302x.2003.00064.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal pathogens in subgingival plaque of HIV‐positive subjects with chronic periodontitis

Abstract: Many putative periodontal pathogens associated with periodontal disease in human immunodeficiency virus (HIV)-infected patients also occur in non-HIV-infected individuals. This study examined the prevalence of eight periodontal pathogens in HIV-positive and HIV-negative patients with chronic periodontitis using the 16s RNA polymerase chain reaction technique. The results showed a significant prevalence of Porphyromonas gingivalis and Treponema denticola among HIV-negative patients compared to HIV-positive pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
2
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 20 publications
(23 reference statements)
1
52
2
1
Order By: Relevance
“…Results from independent studies indicate that periodontopathogens, including P. gingivalis, were detected more frequently and were found at higher levels in HIV-infected patients than in noninfected control subjects with similar periodontal statuses (5,20,26,33). On the contrary, recent results from Patel et al (23) showed a significant prevalence of Porphyromonas gingivalis and Treponema denticola among HIV-negative patients compared to that among HIV-positive patients. Thus, it is possible that P. gingivalis and HIV infections might coexist in the oral cavity, especially in HIV-positive periodontitis patients.…”
Section: Discussionmentioning
confidence: 41%
“…Results from independent studies indicate that periodontopathogens, including P. gingivalis, were detected more frequently and were found at higher levels in HIV-infected patients than in noninfected control subjects with similar periodontal statuses (5,20,26,33). On the contrary, recent results from Patel et al (23) showed a significant prevalence of Porphyromonas gingivalis and Treponema denticola among HIV-negative patients compared to that among HIV-positive patients. Thus, it is possible that P. gingivalis and HIV infections might coexist in the oral cavity, especially in HIV-positive periodontitis patients.…”
Section: Discussionmentioning
confidence: 41%
“…It has been suggested that the loss of CD4+ T-lymphocytes and subsequent immunosuppression in HIV-infected individuals could compromise normal mucosal responses to oral microorganisms, resulting in an elevated colonization of cariogenic and periodontal pathogens or an alteration of the oral microbial community (Patel et al, 2003;Gonçalves et al, 2004Gonçalves et al, , 2007Aas et al, 2007;Saxena et al, 2012). Those changes could be contributing factors for the development of HIV-associated oral diseases, including increased prevalence of dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…HIV-positive individuals are at greater risk of dental caries and periodontal diseases than are HIV-negative individuals (71)(72)(73). The increased risk may be caused by depletion of CD4 ϩ and CD8 ϩ lymphocytes and resultant decreased host immune responses (16,74), increased S. mutans colonization (16), reduced salivary secretion (75,76), and/or poor oral hygiene (77).…”
Section: Discussionmentioning
confidence: 99%